2010
DOI: 10.1007/s10705-010-9404-2
|View full text |Cite
|
Sign up to set email alerts
|

Legume cover crops and mulches: effects on nitrate leaching and nitrogen input in a pepper crop (Capsicum annuum L.)

Abstract: There is not sufficient knowledge concerning the risks involved in NO 3 -N leaching in relation to the use of cover crops and mulches. A 2 year field experiment was carried out in a pepper (Capsicum annuum L.) crop transplanted into different soil management treatments which involved the addition of mulch of three different types of winter cover crops (CC) [hairy vetch (Vicia villosa Roth.), subclover (Trifolium subterraneum L.), and a mixture of hairy vetch/oat (Avena sativa L.)], and an unmulched plot. At th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 45 publications
4
28
0
Order By: Relevance
“…However, when incorporated into the soil hairy vetch residues can release a large amount of mineral nitrogen in a short period of time (Kuo and Sainju, 1998) which makes it difficult to synchronize the nitrogen uptake of the crop especially in summer vegetables such as eggplant which showed a slow growth in the first period after transplanting. Therefore, the high amount of nitrogen released from the hairy vetch cover crop, especially when soil-incorporated in conventional tillage (CT), may be lost if it is not caught by the subsequent crop, while leaving the residues on the soil surface as organic dead mulch can be a viable management practice to delay the mineralization process (Campiglia et al, 2010b). Moreover mulch can increase soil moisture content and stabilize temperature fluctuations that improve nitrogen utilization by the eggplant crop (Sainju et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, when incorporated into the soil hairy vetch residues can release a large amount of mineral nitrogen in a short period of time (Kuo and Sainju, 1998) which makes it difficult to synchronize the nitrogen uptake of the crop especially in summer vegetables such as eggplant which showed a slow growth in the first period after transplanting. Therefore, the high amount of nitrogen released from the hairy vetch cover crop, especially when soil-incorporated in conventional tillage (CT), may be lost if it is not caught by the subsequent crop, while leaving the residues on the soil surface as organic dead mulch can be a viable management practice to delay the mineralization process (Campiglia et al, 2010b). Moreover mulch can increase soil moisture content and stabilize temperature fluctuations that improve nitrogen utilization by the eggplant crop (Sainju et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that grain yields of the primary crop can be improved by incorporation of legume-non-legume mixtures (Doltra & Olesen, 2013) or legume (Campiglia et al, 2011) cover crops. Both legume and non-legume cover crops decreased grain yields but legumenon-legume mixed cover crops increased yield significantly (by ≈13%).…”
Section: Impacts Of Cover Crops (Legume Nonlegume and Legume-non-lmentioning
confidence: 99%
“…Cultivation affects decomposition and mineralization of existing soil organic N pools and plant residues, providing a pool of inorganic N for vine uptake (Calderón et al 2001). Quality and quantity of incorporated plant residues also will inf luence the timing of N release relative to vine demand (Campiglia et al 2011).…”
Section: Cultivationmentioning
confidence: 99%